Analisis Kelayakan Finansial Usahatani Pembenihan Ikan Nila (Oreochromis Niloticus) di Desa Selajambe Kecamatan Cisaat Kabupaten Sukabumi - Shofa Hanis Aisyah; Kuswarini Sulandjari; Suhaeni Suhaeni (Jurnal Ilmiah Wahana Pendidikan, 2021)
Tilapia (Oreochromis niloticus) is one of the fishery commodities that have a high economic value. This study aims to find out the cost and income, financial feasibility and sensitivity of the feasibility of tilapia seeding business. The research method used is a quantitative method by conducting a survey. Primary data collection through interviews and observations. The study respondents were tilapia seed farmers, leaders of farming groups, extensionists and other sources. Sampling uses the Cluster Sampling method as a consideration of the age of tilapia parentage. The analytical techniques used are: cost and income analysis, Net Present Value, Internal of Return, Gross B/C Ratio, Net B/C Ratio, Payback Period, R/C Ratio, and sensitivity analysis. Research results: Tilapia breeding business from year 1 to 4 per 1000 costs Rp24,927,590, resulting in receipt of Rp27,106,725 with an interest rate of 6% obtained NPV Rp11,751,081, IRR 67%, Payback Period for 1 year, Gross B /C of 1,541, Net B/C of 3,751 and R/C ratio of 1,263. It means it's worth working on. The 2% increase in production costs resulted in NPV Rp11,598,788, IRR 66%, Payback Period for 1 year, Gross B/C 1,531, Net B/C of 3,715. A 25% decrease in receipts resulted in NPV Rp6,020,963, IRR 40% Payback Period for 1 Year 5 Months 25 days, Gross B/C 1,277, Net B/C 2,410, still included worthy.